A multi-environment trials diallel analysis provides insights on the inheritance of fumonisin contamination resistance in tropical maize - Ribeiro, Carlos Alexandre Gomes; Pádua, José Maria Villela; Dias, Kaio Olímpio das Graças; Pastina, Maria Marta; Souza, João Cândido de; Queiroz, Valéria Aparecida Vieira; Costa, Rodrigo Veras da; Silva, Maria Beatriz Pereira da; Guimarães, Claudia Teixeira; Gezan, Salvador Alejandro; Guimarães, Lauro José Moreira (Euphytica, 2016)
In maize, the fungi that cause Fusarium ear rot result not only in decreased grain yield and quality, but also grain contamination by fumonisin. This study investigated the inheritance of fumonisin contamination resistance (FCR) in tropical maize, based on a multi-environment trials diallel analysis via mixed models. For this purpose, based on 13 inbred lines, single-cross hybrids were created and assessed in three environments. A mixed model diallel joint analysis across environments was performed, considering the existence of environment-specific variances and correlations between pairs of environments for general combining ability (GCA) and specific combining ability (SCA) effects, and additive genomic relationship between inbred lines for the prediction of GCA and SCA. For all environments, the SCA variance had a higher magnitude than the GCA variance, indicating a predominance of the dominance effects underlying FCR in tropical maize. Moreover, the proportion of the variance among single-cross hybrids that was due to GCA varied from 16 to 22 % across environments, suggesting that SCA is important to predict the hybrids performance. Through modeling variance–covariance structures for GCA and SCA, it was possible to observe that the GCA effects were stable, whereas the SCA effects were specific for each environment. Therefore, these results suggest that the selection of the best parents for the development of new inbred lines can be carried out through the average performance across the evaluated environments. Due to the importance of SCA effects and their complex interaction with environments, the selection of superior hybrids should be performed into specific environments.
Keywords: Zea mays; Mycotoxins; Linear mixed models; Variance–covariance structures; Additive genomic relationship matrix